2023
DOI: 10.3233/jad-220666
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Pathophysiology of Alzheimer’s Disease and Potential Therapeutic Targets: A Current Perspective

Abstract: The aging population increases steadily because of a healthy lifestyle and medical advancements in healthcare. However, Alzheimer’s disease (AD) is becoming more common and problematic among older adults. AD-related cases show an increasing trend annually, and the younger age population may also be at risk of developing this disorder. AD constitutes a primary form of dementia, an irreversible and progressive brain disorder that steadily damages cognitive functions and the ability to perform daily tasks. Later … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 249 publications
2
9
0
Order By: Relevance
“…indicating hypoexcitation, whole-brain models informed with neurotransmitters and neuromodulator receptor expression could be used to test pharmacological interventions that may restore a healthy E/I balance in patients. Possible candidates include cholinergic drugs 107,128 and psychedelics, 129 which have been found to restore normal brain function in other disorders. 130 From a more methodological perspective, our work provides valuable computational tools for studying whole-brain dynamics in both health and disease, 11 and we have made these tools publicly available alongside this publication.…”
Section: Discussionmentioning
confidence: 99%
“…indicating hypoexcitation, whole-brain models informed with neurotransmitters and neuromodulator receptor expression could be used to test pharmacological interventions that may restore a healthy E/I balance in patients. Possible candidates include cholinergic drugs 107,128 and psychedelics, 129 which have been found to restore normal brain function in other disorders. 130 From a more methodological perspective, our work provides valuable computational tools for studying whole-brain dynamics in both health and disease, 11 and we have made these tools publicly available alongside this publication.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the unequivocal role of Aβ in AD pathogenesis, it is unclear if Aβ functions as the predominant driving force in AD pathology, and has a greater effect compared to the contributions of pathogenic tau or neuroimmune responses. The pathophysiologic heterogeneity and involvement of other microenvironmental and individual variability in responding to the amyloid load, may explain the differences in the trial results 5 . In the clinical trial of donanemab, significant clinical benefits were observed in the participants in the low/medium tau group presenting stable scores of the CDR‐SB at 1 year, but this was not noticed in the high tau group 6 .…”
Section: Figurementioning
confidence: 99%
“…The pathophysiologic heterogeneity and involvement of other microenvironmental and individual variability in responding to the amyloid load, may explain the differences in the trial results. 5 In the clinical trial of donanemab, significant clinical benefits were observed in the participants in the low/medium tau group presenting stable scores of the CDR-SB at 1 year, but this was not noticed in the high tau group. 6 Hence, clinical and genetic heterogeneity in the AD population, coupled with variable intrinsic rate of AD decline could account for the negative findings in the gantenerumab clinical trials, which may represent a potential type II error.…”
mentioning
confidence: 97%
“…As the disease progresses, social, occupational, and life functions will be severely affected, more severely, patients will die of complications within 10–20 years after onset. Based on this, AD and other dementias were considered as the seventh leading cause of death globally, with a dramatic 174% increase from 2000 (Kumaran et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…were considered as the seventh leading cause of death globally, with a dramatic 174% increase from 2000 (Kumaran et al, 2023).…”
mentioning
confidence: 99%